Extraction and storage stability of red color from Roselle (Hibiscus sabdariffa) - Oarde, Cynthia M.; del Valle, Mercedita (1978.)
The study was undertaken to extract a natural red pigment from roselle calyxes and determine its storage stability under different pH and temperature conditions. Extraction of pigment was made according to the procedure used for sugar beets by Vidal-Adeva (1996) except for the method of concentration used. The crude pigment concentrate obtained had a translucent bright red color, a pH of 2.45, an average soluble solids content of 9.5% and gave maximum absorption at a wavelength of 520 mu. The results of storage studies for a period of two months under different condition of pH and temperature showed that the pigment is most stable at its natural pH of 2.45 and when stored at refrigeration temperature (5-10°C).
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coloring matter in food; Roselle